Oncology medications prescription in a cancer service: appropriateness to clinical practice guidelines - Valeria Palchik; María Luz Traverso; Marisel Colautti; Mariela Bianchi; Lucía Dolza; José María Catena; Mercedes Salamano (Elsevier, 2016)
Objective: To assess prescription of oncology medications in municipal public health network of Rosario for its appropriateness to clinical practice guidelines. Methods: Descriptive pharmacoepidemiological study in adult patients in an Oncology Service between January and June 2012. Compliance requirements with clinical practice guidelines were evaluated. Results: 51.8% of diagnoses had at least one prescription medication that did not match recommendation by at least one of the guides considered. Prescriptions of doxorrubicine and ifosfamide did not agree with the recommendation of any reference guides. 5.4% of prescriptions weren´t considered by local guides, nor 7.7% by national on es. Regarding comparison with international guidelines: 4.2% of prescriptions weren ´t considered by the European Society for Medical Oncology guidelines, 2.3% not considered by the American Cancer Society and only 1.9% were not considered by the National Comprehensive Cancer Network ones. Conclusions: Prescription of oncology treatments is closer to international reference guides. One reason could be that there is still no standard definition in the management of tumor diseases by the National State.